1997
DOI: 10.1177/030089169708300617
|View full text |Cite
|
Sign up to set email alerts
|

Cancer of the Appendix in Long-Standing Ulcerative Colitis: A Case Report

Abstract: Cancer of the appendix was found in a 69-year-old female patient affected by long-standing ulcerative colitis (UC). On histological examination the cancer was a typical cystadenocarcinoma of the appendix. The appendiceal mucosa not invaded by the neoplastic process was normal. Histological examination of the colorectal mucosa did not show dysplasia or cancer. These findings suggest that appendiceal cancer and UC may be unrelated diseases. A surveillance program for early detection of cancer of the appendix in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 5 publications
1
7
0
1
Order By: Relevance
“…Our patient's case is the first one reported in Mexico and supports Zannoni et al's description of 1997 [6]. We did not identify in the surgical specimen pancolonic affection or a cecal appendix involvement related to ulcerative colitis; we did not even identify any chronic inflammatory change in the proximal colon, suggesting a previous pancolonic affection.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Our patient's case is the first one reported in Mexico and supports Zannoni et al's description of 1997 [6]. We did not identify in the surgical specimen pancolonic affection or a cecal appendix involvement related to ulcerative colitis; we did not even identify any chronic inflammatory change in the proximal colon, suggesting a previous pancolonic affection.…”
Section: Discussionsupporting
confidence: 84%
“…In 1997, Zannoni et al [6] reported a patient with a long evolved UC history who developed a cystadenocarcinoma of the appendix where no appendix affection was found related to UC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Although appendiceal inflammation occurs histologically in 40%-86% of colectomy specimens from patients with IBD, 4 -10 appendiceal neoplasms have been reported only infrequently, [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] and the notion of a direct association between IBD and appendiceal neoplasia is speculative.…”
Section: (Inflamm Bowel Dis 2009;15:415-421)mentioning
confidence: 99%
“…The extent and duration of disease are directly related to the increased risk. Although the appendix has been shown to be involved in more than 50% of cases of pancolitis [4], only four cases of appendiceal carcinoma associated with UC have been published [5,6,7,8]. All four cases had long-standing UC.…”
mentioning
confidence: 99%